2019
DOI: 10.3389/fpls.2019.01049
|View full text |Cite|
|
Sign up to set email alerts
|

Accumulation of Anthocyanins: An Adaptation Strategy of Mikania micrantha to Low Temperature in Winter

Abstract: The accumulation of anthocyanins in leaves and stems of Mikania micrantha improves its adaptability to low-temperature environments during winter in areas where this species is invasive. The accumulation of anthocyanins in M. micrantha causes the plants to exhibit red coloration when encountering low-temperature environments during winter. Many studies have reported that the accumulation of anthocyanins near the plant surface filters light and improves photoprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 45 publications
4
51
0
Order By: Relevance
“…5); the former of which could decrease light absorption and better remove ROS generated in plants (Zhu et al 2018). These results were consistent with the findings by which the cold resistance of Begonia semperflorens obviously improved when the anthocyanin content increased (Zhang et al 2019). In addition, the contents of soluble sugars in leaves and stems increased significantly under low temperature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…5); the former of which could decrease light absorption and better remove ROS generated in plants (Zhu et al 2018). These results were consistent with the findings by which the cold resistance of Begonia semperflorens obviously improved when the anthocyanin content increased (Zhang et al 2019). In addition, the contents of soluble sugars in leaves and stems increased significantly under low temperature.…”
Section: Discussionsupporting
confidence: 88%
“…Plants can generally improve their resistance to adversity by inducing metabolic activities in their cells to adapt to low temperature and increase cold resistance at certain temperatures (Liu et al 2013). Studies have shown that low temperature can induce anthocyanin accumulation (Chang et al 1989, Carmona et al 2017, Zhang et al 2019. The results showed that the stems could accumulate more anthocyanins than the leaves (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…2 F,G), which indicated that the high photosynthetic capacity was related to its strong electron transfer ability 26 . It has been well acknowledged that Chl and Rubisco have often been considered indices of the light-harvesting and Calvin cycle capacities of leaves, respectively, which play an important role in photosynthesis capacity 30 – 32 . The leaves of S. trilobata had higher Chl and Rubisco contents than those of S. calendulacea , which was consistent with the trend observed for P n (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 H). This could effectively prevent excess light energy from damaging the light system 30 . In contrast, the Chl a/b and Car/Chl ratio in S. trilobata were lower than those in the native species (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is a species that prefers higher temperatures and high-light environments. In order to adapt to the low-temperature (below 15 °C) environment in the winter in South China (a region where M. micrantha had spread into), anthocyanins were accumulated in M. micrantha leaves [20]. However, anthocyanin can reduce the absorbance of light by plant leaves [12], and through this mechanism, the low-light environment can affect the growth of M. micrantha [21].…”
Section: Introductionmentioning
confidence: 99%